Implications of the coronavirus pandemic for the internal policy of the European Union. (Economic and Political Thought, 2022)
The aim of this article is to indicate the actions of the European Union to combat the effects of the coronavirus pandemy and present the activities of politicians in the period from the beginning of 2020 until the second half of 2022. European Union struggled with the problems of systemic, economic and politicial nature. First months of pandemy showed us weakness in responding to coronavirus which threated politicians of UE. Invidual countries were even forced to cope on their own and do activities not frequently common with EU agenda that was characterized by solidarity and the proclamation of cooperation. European initiatives consisting in loosening the rules of state aid, providing the “EU Recovery Plan for Europe”, introduce mass campaign action of vaccination, activities in the field of medicine and implementing of the “EU COVID Certificate” are the result of the conclusion that the measures must be adapted to the current pandemic situation which affects multitude of public life areas.
Keywords: coronavirus, European Union, Community, society, health, eurozone